Radar : the silent detector - Hitzeroth, Deborah, 1961- (San Diego, CA : Lucent Books, 1990)
Examines the invention and development of radar, its history, and its uses in science, law enforcement, navigation, space travel, and the military.
Includes bibliographical references (p. 89-90) and index.
School Library Journal.
Wilson's Junior High School.
7.4
5-8
7-9
Keywords: Radar -- Juvenile literature; Radar; Radar